The impact of sudden changes in raw water quality on the operation of a conventional water treatment system ‒ a case study - Gumińska, Jolanta; Kłos, Marcin (Instal, 2025)
Under conditions of high variability in raw water quality, the analyzed technological system, operating on the basis of coagulation/flocculation, sedimentation, and rapid filtration processes in existing water treatment plant equipment, does not allow for stable operation of the technological system. This is most noticeable during periods when raw water turbidity increases from approximately 5 to a maximum of 114 NTU within a few hours. In the clarified water, a rapid increase in the turbidity of the water after the settling tank was also noted, up to 14.5 NTU, compared to the period preceding the sudden deterioration in the quality of the water feeding the system. The colour of the raw water varied between 12 and 180 gPt/m3. The clarified water showed a colour of 4 and 40 gPt/m3, resulting from the colour changes in the raw water. The colour of the filtered water varied between 1 and 13 Pt/m3. This is primarily due to the lack of optimal flocculation and sedimentation equipment, i.e., the low hydraulic efficiency of the settling tanks integrated with the vertical flocculation chambers. Therefore, in case of a sudden deterioration in raw water quality, the filters retained the excessive suspended solids that were not retained in the settling tanks. It was also shown that the permanganate index cannot be a reliable indicator for assessing the effectiveness of water treatment in the analyzed technological system.